EVALUATION OF THE LEVEL OF ROAD DAMAGE IN JELIDRO II-KUWUKAN-SAMBIKEREP ROADS USING THE PAVEMENT CONDITION INDEX (PCI) AND BINA MARGA METHOD - Thasyara Nurhijriyah; Kurnia Hadi Putra; Theresia Maria Chandra Agusdini (Journal Innovation of Civil Engineering (JICE), 2024)
The road is a facility for land transportation that serves regional development. The deterioration of road quality can pose constraints on economic and social activities and endanger road users. Small damages can escalate if not promptly addressed, leading to losses. This reasearch aims to determine the type and level of damage on Jelidro II – Kuwukan - Sambikerep Roads STA 0+000 to STA 1+600. There are two methods for obtaining road condition values in this research, the methods are Pavement Condition Index method and the Bina Marga method. On the section of Jelidro II – Kuwukan - Sambikerep Roads, 8 types of damage were found, those are crocodile skin cracks, grade depression, edge cracks, potholes, patches, longitudinal cracks, slip cracks, and ravelling. The results of calculating the road condition value using the PCI method is 63,6 where the road is included in the good category. Calculations using the Bina Marga method get a priority order of 9. The two methods show that the road has the same type of treatment, that is a routine maintenance program with repair methods that can be carried out, namely surface layers such as asphalt resurfacing and patching holes. Keywords: Road Damage; PCI method; Bina Marga method.